Oncoplastic Lower Eyelid Reconstruction Analysis. Issue 8 (November 2019) - Orgun, Doruk; Hayashi, Ayato; Yoshizawa, Hidekazu; Shimizu, Azusa; Horiguchi, Masatoshi; Mochizuki, Mariko; Kamimori, Tomoki; Aiba-Kojima, Emiko; Mizuno, Hiroshi
Abstract : Background: Oncoplastic lower eyelid reconstruction is a challenging task due to the complicated structure of the eyelid and requirement of high operative accuracy. Poorly treated defects result in ectropion and ptosis which may lead to keratitis and corneal ulceration. Previous related studies do not include a detailed comparison of the common reconstructive methods of the lower eyelid in terms of results and complication rates. Objective: The authors aim to demonstrate whether the choice of reconstruction affects the aesthetic and functional outcome of oncoplastic lower eyelid reconstruction. Methods & Materials: The authors performed a 10-year retrospective review of all oncoplastic lower eyelid reconstructions carried out in our hospital. Information on patient background, diagnosis and the choice of reconstructive method were evaluated. Postoperative photographs of each patient were then subjectively evaluated for color match, cosmesis, quality of shape, symmetry, and overall appearance. The authors hypothesized that the outcome is related to the main trajectory of the flap. Patients treated with local flaps of horizontal and vertical trajectories were then compared in terms of outcome and complication rates. Results: Reconstructions based on a horizontal trajectory compared with a vertical trajectory resulted with lower rates of ectropion and ptosis occurrence. The results were statistically significant. Abstract : Supplemental Digital Content is available in the text